1999
DOI: 10.1097/00006123-199904000-00101
|View full text |Cite
|
Sign up to set email alerts
|

Infratentorial Subdural Empyema, Pituitary Abscess, and Septic Cavernous Sinus Thrombophlebitis Secondary to Paranasal Sinusitis: Case Report

Abstract: Paranasal sinusitis can have devastating intracranial sequelae. Involvement of the adjacent pituitary gland and cavernous sinuses can result in serious neurological morbidity or mortality, and retrograde spread of infection through the basal venous system can result in subdural or parenchymal brain involvement. A high index of suspicion and aggressive medical and surgical treatment are crucial for patient survival, but the morbidity rate remains high. Our patient survived but lost anterior pituitary function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…However, majority of adenomas will have more solid enhancement as opposed to thin rim in case of an abscess [14]. Presence of air fluid level, meningeal enhancement, cerebritis, sphenoid sinus effusion or destruction of its floor, absence of posterior pituitary bright spot, cavernous sinus thrombosis are supportive towards an abscess [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, majority of adenomas will have more solid enhancement as opposed to thin rim in case of an abscess [14]. Presence of air fluid level, meningeal enhancement, cerebritis, sphenoid sinus effusion or destruction of its floor, absence of posterior pituitary bright spot, cavernous sinus thrombosis are supportive towards an abscess [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A previous case of three different intracranial extensions (infratentorial empyema, pituitary abscess, and septic cavernous sinus thrombophlebitis) secondary to paranasal sinusitis showed septic cavernous sinus thrombophlebitis extended to the clivus. 19) Orbital SPA and intracranial extension from paranasal sinusitis has not been reported. This complicated pathogenesis made the diagnosis very difficult in our case.…”
Section: Discussionmentioning
confidence: 99%
“…In 1993, Bok and Peter [6] conducted a retrospective study of 90 cases with subdural empyema and found 34 and 4 cases, respectively, located at the interhemispheric (37%) and posterior fossa (4%), whereas the case series reported by Nathoo et al [13] found that only 1 patient (0.5%) developed infratentorial empyema secondary to paranasal sinusitis. In 1999, Sahjpaul and Lee [14] also described a case of infratentorial subdural empyema secondary to paranasal sinusitis with pituitary abscess and septic cavernous sinus thrombophlebitis. Our patient suffered subdural empyema located in the interhemispheric and infratentorial regions.…”
Section: Discussionmentioning
confidence: 99%